Cryptocurrency: An Islamic Finance Perspective - Nabeel. K, Mohammed; Sumathy, M. (Al-Muhasib: Journal of Islamic Accounting and Finance, 2023)
The popularity of virtual currencies has increased markedly in recent years. Seminars and conferences have explored the properties and sustainability of cryptocurrencies. Some argue that an alternative to the current fiat currency system would be beneficial, as it would not mandate the use of a bank account, tax payments, or audits as do the said cryptocurrencies. Alternative methods of payment, aside from those commonly accepted like cash, checks, and DD, have been claimed to enable tax and auditing avoidance. However, this view has been contested, given the potential negative impact on the economy and the government budget. The present study addresses the challenges and limitations involved in considering bitcoins to be halal. It has been determined that cryptocurrencies are not considered Halal in Islam because they lack intrinsic value and are subject to significant regulatory oversight. Popularitas mata uang virtual telah meningkat pesat dalam beberapa tahun terakhir. Seminar dan konferensi telah mengeksplorasi properti dan keberlanjutan mata uang kripto. Beberapa orang berpendapat bahwa alternatif dari sistem mata uang fiat saat ini akan bermanfaat, karena tidak mengharuskan penggunaan rekening bank, pembayaran pajak, atau audit seperti halnya mata uang kripto. Metode pembayaran alternatif, selain dari yang umum diterima seperti uang tunai, cek, dan DD, telah diklaim memungkinkan penghindaran pajak dan audit. Namun, pandangan ini telah diperdebatkan, mengingat potensi dampak negatifnya terhadap ekonomi dan anggaran pemerintah. Penelitian ini membahas tantangan dan keterbatasan yang terlibat dalam mempertimbangkan bitcoin sebagai sesuatu yang halal. Telah ditetapkan bahwa mata uang kripto tidak dianggap halal dalam Islam karena tidak memiliki nilai intrinsik dan tunduk pada pengawasan regulasi yang signifikan.